Adhesive properties of predominant bacteria in raw cow's milk to bovine mammary gland epithelial cells - Hagi, Tatsuro; Sasaki, Keisuke; Aso, Hisashi; Nomura, Masaru (Folia microbiologica, 2013)
Various bacteria have been found in raw cow's milk, and identifying milk microflora and its functions is critical for maintaining cow health and farm hygiene. Although studies on pathogens and spoilage bacteria in milk have been widely reported, the relationship between milk bacteria, including nonpathogenic bacteria, and the bovine udder is poorly understood. We investigated milk microflora over 1 year using a culture-dependent method and culture-independent analysis by denaturing gradient gel electrophoresis. Among 240 isolates, Lactococcus lactis (81/240) was predominant. The predominant genera were Lactococcus, Stenotrophomonas, Microbacterium, Chryseobacterium, Serratia and Pseudomonas. Among seven strains belonging to these predominant genera, two strains of L. lactis (ssp. lactis and ssp. cremoris) exhibited the highest adherence to bovine mammary gland epithelial cells (BMECs) derived from the bovine udder; 3.4 % of the inoculated bacteria adhered to BMECs. This was followed by Serratia sp. (1.6 %), Microbacterium sp. (0.8 %), Stenotrophomonas maltophilia (0.5 %), Pseudomonas sp. (0.3 %) and Chryseobacterium sp. (0.1 %). The two L. lactis isolates exhibited higher adherence to BMECs than type strains and isolates of various origins.
Keywords: Biodiversity; Cattle; epitelové buňky; RNA, Ribosomal, 16S; skot; Sequence Analysis, DNA; Epithelial Cells; Bacterial Adhesion; Mammary Glands, Animal; ribozomální DNA; biodiverzita; sekvenční analýza DNA; Bacteria; molekulární sekvence - údaje; Bacterial Physiological Phenomena; mléčné žlázy zvířat; DNA, Bacterial; DNA bakterií; Animals; zvířata; mléko; RNA ribozomální 16S; Molecular Sequence Data; DNA, Ribosomal; bakteriální adheze; fyziologie bakterií; Milk